Hydrodynamic regime determines the feeding success of larval fish through the modulation of strike kinematics. Issue 1853 (26th April 2017) - China, Victor; Levy, Liraz; Liberzon, Alex; Elmaliach, Tal; Holzman, Roi
Abstract : Larval fishes experience extreme mortality rates, with 99% of a cohort perishing within days after starting to actively feed. While recent evidence suggests that hydrodynamic factors contribute to constraining larval feeding during early ontogeny, feeding is a complex process that involves numerous interacting behavioural and biomechanical components. How these components change throughout ontogeny and how they contribute to feeding remain unclear. Using 339 observations of larval feeding attempts, we quantified the effects of morphological and behavioural traits on feeding success of Sparus aurata larvae during early ontogeny. Feeding success was determined using high-speed videography, under both natural and increased water viscosity treatments. Successful strikes were characterized by Reynolds numbers that were an order of magnitude higher than those of failed strikes. The pattern of increasing strike success with increasing age was driven by the ontogeny of traits that facilitate the transition to higher Reynolds numbers. Hence, the physical growth of a larva plays an important role in its transition to a hydrodynamic regime of higher Reynolds numbers, in which suction feeding is more effective.